2003
DOI: 10.1109/jlt.2003.817711
|View full text |Cite
|
Sign up to set email alerts
|

High-bandwidth graded-index polymer optical fiber enabling power penalty-free gigabit data transmission

Abstract: A relation between the 3 dB bandwidths of graded-index plastic optical fibers (GI POFs) and the total power penalty of 50-m GI POF links is investigated in detail. The bandwidth of the GI POF is deliberately varied by controlling the index profile. It is theoretically and experimentally confirmed that sufficiently high bandwidth on the order of gigahertz is necessary for the GI POF, even for several hundreds of megabit per second (Mb/s) data rate, in order to achieve the power penalty free in the bit error rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Previous results [5] have demonstrated that PF GIPOF and 62.5/125 GOF penalties due to modal dispersion and noise are similar in gigabit Ethernet transmission at 850 nm with COTS GOF components. Moreover, because of its higher core diameter, PF GIPOF does not induce modal noise penalties as occurred in glass optical multimode fibre link [6] and the alignment is also less critical, which reduces the cost of the optical active and passive devices, including the installation and maintenance cost of the connections. Its higher flexibility based on "plastic" material offers a great advantage compared to the silica fibre, which is more brittle.…”
Section: Discussionmentioning
confidence: 99%
“…Previous results [5] have demonstrated that PF GIPOF and 62.5/125 GOF penalties due to modal dispersion and noise are similar in gigabit Ethernet transmission at 850 nm with COTS GOF components. Moreover, because of its higher core diameter, PF GIPOF does not induce modal noise penalties as occurred in glass optical multimode fibre link [6] and the alignment is also less critical, which reduces the cost of the optical active and passive devices, including the installation and maintenance cost of the connections. Its higher flexibility based on "plastic" material offers a great advantage compared to the silica fibre, which is more brittle.…”
Section: Discussionmentioning
confidence: 99%
“…The results show that the Lucina fiber constitutes without any doubt a promising candidate in RoF system using commercially available components manufactured for glass fibers. Moreover, because of its higher core diameter, POF does not induce modal noise penalties as in glass multimode fiber links [28] and the alignment is also less critical, thus reducing the cost of the optical active and passive devices including the installation and maintenance costs of the connections. Its higher flexibility based on -plastic‖ material offers a great advantage compared to the silica fiber which is more brittle.…”
Section: Radio Over Fiber System With Pfgi-pofmentioning
confidence: 99%
“…Values of g = 2 are typically cited (Ishigure et al 1996, Ishigure et al 2003 as optimal with respect to maximising bandwidth. In the move to microstructured multimode fibres, the idea of a graded index can be retained since a large array of holes can be designed to approximate a circularly symmetric parabolic profilen(r).…”
Section: 61mentioning
confidence: 99%